Redes interorganizacionais: uma análise das razões de saída das empresas parceiras - Lima, Patricia Ennes da Silva (2007)
The development of interorganisational cooperation networks is increasingly exalted as a growing alternative. Its importance is strongly visible regarding the small and medium size enterprises that, because of the great competitiveness existent, can t act separately, so, they become ruled by the market. The fact is that the networks only get great advantages if several conditions are fulfilled, which makes the process a little more complex. Anyway, most studies, with some exceptions, asserts that this is an excellent opportunity of stableness and even of increasing in the market where the enterprises are inserted. Even though from the empirical view-point, one can observe an expressive number of enterprises which leave the cooperative process.This exploratory study of qualitative character objective to find out the reasons that lead the enterprise decision to leave the network, because it can be an alternative for minimizing the problems that emerge during the associative process and that make impossible the extent of the stipulated objectives. Therefore, there were interviews with: 1) five enterprises of pharmacy branch which had participated in a specific network; 2) the interorganisational network and; 3) a new format of interorganisational network to which most of enterprises migrated, all of them located in the state of Rio Grande do Sul. From these interviews it could compare and confront different situations and perceptions of enterprise and network, arriving the pertinent analyses regarding the network problems, the associate enterprise profile, the selective process practiced in the associativist movement and the reasons that lead the enterprises to leave the networks. In response to this study problematic the results evidenced some variants, to cite: the size of the participant enterprises, information asymmetry, distrust relationship, managing process developed by networks, and the costbenefit relation that results from that movement. Another conclusion resulting from the research evidences that the network format and verifies that its survival is related to the managing features which are many times argued by associated enterprises: rigid rules and minimal share of purchasing by associate, this guarantee the bargain power which so many enterprises look for in the associativist process. All these variables, according to the evidences from these analyses, influence in the enterprise decisions for staying or not in the network. And they can support the networks which look for the success in their cooperations. This way, the reason diagnosis that lead an enterprise to leave the network to which it belonged, contributes to all stages that constitute the network development. This involves since the creation of its statute, formalization of its contracts and choice of its associates. It has even the possibility to accomplish the withdrawal of some enterprise for dissastisfaction or other motive, in a less disturbed and traumatic way for both parts.